(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the formation of ancient horse breeds that existed in Central Asia, their classification based on biological and morphological characteristics, and their representation in historical sources. Drawing upon ancient written monuments, archaeological discoveries, and numismatic materials, the study highlights the culture of horse breeding in Central Asia and the role of horses in social and military life. Comparative analysis has been conducted using various historical sources, including Chinese chronicles, works of Greco-Roman authors, and writings of Arab and Persian historians. The results of the research demonstrate that ancient horse breeds of Central Asia were not only an integral part of the region’s economic life but also played a significant role in the cultural and political development of its peoples